Focus Group Discussion How to Quickly Build Students' Critical Thinking Skills - Abidin, Zaenal; Shah, Zubair Ahmad; Rauf , Muhammad (Zabags International Journal of Education, 2025)
This study aims to focus on Group Discussion: How to Quickly Build Students' Critical Thinking Skills. It includes how this strategy can be implemented more optimally at various levels of education and learning contexts for students of the Elementary Madrasah Teacher Education Study Program, Al-Mujaddid Sabak Islamic Institute. In discussing the theme of Focus Group Discussion as an Effective Strategy in Developing Critical Thinking Skills in Students, the appropriate research method is qualitative research with a descriptive approach and in-depth interviews. It can be concluded that the implementation of Focus Group Discussion (FGD) as a learning strategy in the Educational Management course at the Elementary Madrasah Teacher Education Study Program, Al-Mujaddid Sabak Islamic Institute, is very effective in developing students' critical thinking skills. Through a collaborative, interactive, and reflective discussion process, students are actively involved in expressing and evaluating various perspectives, as well as analyzing real cases in educational management. FGD not only helps students understand educational management theory more deeply but also trains them to think critically in dealing with complex situations in the real world. Although there are challenges in its implementation, the role of lecturers as facilitators and creators of an inclusive discussion atmosphere can overcome these obstacles, so that FGD can be carried out more optimally.